Pediatric firearm injury related emergency department visits and hospitalizations: a population-based study in the United StatesResearch in context - Ruchika Goel; Xianming Zhu; Sarah Makhani; Cassandra D. Josephson; Jodie L. White; Oliver Karam; Marianne E. Nellis; Eric A. Gehrie; Mingmar Sherpa; Elizabeth P. Crowe; Evan M. Bloch; Aaron A.R. Tobian (Elsevier, 2023)
Summary: Background: Firearm injury (FI) is the leading cause of death in children and adolescents in the United States (US). We describe the epidemiology of pediatric FI-associated emergency department (ED) visits and hospitalizations in the US stratified by race and ethnicity. Methods: Data on pediatric (0-17-year-olds) FI were analyzed using the 2019 Nationwide Emergency Department Sample (NEDS) and Kids' Inpatient Database (KID), the largest all-payer databases in the US for ED visits and pediatric hospitalizations, respectively. FI encounters were stratified by race and ethnicity. Poisson regression was used to identify factors associated with in-hospital mortality. Sampling weights were applied to generate nationally representative estimates. Findings: There were 7017 pediatric ED visits with FI (NEDS); 85.0% (5961/7017) were male and 73.0% (5125/7017) were adolescents (15-17 years). Overall, 5.5% (384/7017) died in the ED; 53.1% (3727/7017) of ED encounters did not result in hospitalization. There were 2817 pediatric FI hospitalizations (KID); 84.1% (2369/2817) were male and 71.6% (2018/2817) were adolescents; 51.4% (1447/2817) of FI were unintentional, 42.8% (1207/2817) were assault-related, and 5.8% (163/2817) were self-inflicted. Black children had the highest proportion (52.6%; 1481/2817) of hospitalizations among all race and ethnicities (p < 0.0001 vs. White). White children had the highest proportion of hospitalizations for self-inflicted injuries (16.6% [91/551] vs. 4.9% [25/504; p < 0.0001] in Hispanics and 1.7% [24/1481] in Blacks; p < 0.0001). The majority (56.5%; 1591/2817) of hospitalizations were patients from low-income zip codes (median annual-household-income <$44,000); 70% (1971/2817) had Medicaid as the primary insurance payer. Overall, 8.0% (225/2817) died during FI-associated hospitalizations. Self-inflicted injuries had the highest in-hospital mortality (prevalence ratio = 8.20, 95% CI = 6.06-11.10 vs. unintentional). Interpretation: Black children and children with lower household incomes were disproportionately impacted by FI resulting from assaults and accidents, while White children had the highest proportion of self-inflicted FI injuries. Public health and legal policy interventions are needed to prevent pediatric FI. Funding: US National Institutes of Health.